Upaya Kepolisian dalam Menanggulangi Tindak Pidana Korupsi - Waspada, Lesta Indra; Muchtar, Syamsuddin; Ilyas, Amir (Universitas Negeri Malang, 2021)
The purpose of this study was to analyze the efforts of the police in overcoming criminal acts of corruption and to analyze the obstacles faced by the police in overcoming criminal acts of corruption. The study used empirical research type. Data collection techniques in this study were through direct interviews with respondents as the primary data source and through literature study as a secondary data source. The data analysis technique used was qualitative technique. The results showed that the efforts made by the police to tackle corruption were in the form of preemptive, preventive, and repressive measures. Preemptive efforts were in the form of educating the public through pamphlets, brochures, and banners that contained all matters relating to corruption. Preventive efforts by way of synergizing with law enforcement officials, improving coordination, investigation, and investigation functions in ten areas prone to corruption, and responding to public demanded to accelerate investigations. Repressive measures in the form of sanctions against corruptors in accordance with the law. The obstacles faced in overcoming corruption were internal constraints, namely the slow disbursement of program budgets for pre-emptive and preventive activities, as well as external obstacles, namely the lack of understanding of corruption by the public.